Desarrollo de un curso virtual de análisis estadístico con el uso del programa spss, como aporte a las actividades prácticas del sílabo de la asignatura de Estadística de la carrera de Informática Educativa de la Universidad Nacional de Loja - Merchan Infante, Christian Andres (2016)
This research work has been carried out based on the detected problem about the lack of management software such as SPSS, and limited information and training in the use of the above mentioned program; this research was conducted at the National University of Loja, located in the canton and province of Loja, cdla. July Ordonez, who participated in the same students of the fifth cycle race on Computers in Education and teaching of the subject of statistics, in which the SPSS program was used as input for the practical activities of the course syllabus of Statistics. The preparation and implementation of the SPSS program was performed according to the ADDIE methodology and each of the phases allowed to successfully fulfill all proposed; also in this research the scientific method, the constructivist pedagogical model and the technique used was a survey to collect data were applied the same as when applied it was found that there are issues with greater difficulty which were calculated relative frequencies, measures of central tendency, measures of dispersion and variability, typing scores, hypothesis testing by statisticians Z, T, Chi square, variable correlation coefficients of Pearson, Spearman and Kendall as well as after developing activities and working with students we proceeded to make socialization and then apply the valuation record to determine the degree of acceptance that has this teaching resource; obtaining satisfactory results proving that this teaching resource is an important support for the subject of Statistics